Pancreatic-Biliary Ascariasis in an Infant - Roy, Kakali; Das, Joydeep; Mukherjee, Devdeep; Kundu, Ritabrata (Journal of Nepal Paediatric Society, 2017)
Ascaris infestation that too causing biliary obstruction is very rare in infancy even in endemic area. Adult Ascaris diameter (3-6 mm) is more than the average diameter of CBD in paediatric population, which is 1.27 +/- 0.67 mm. We are reporting a baby of seven months who presented with conjugated hypebilirubinemia and pancreatitis due to Round Worm in CBD.